At home in time : forms of neo-Augustanism in modern English poetry - Deane, Patrick (McGill-Queens University Press, 1994)
The presence of these values, Deane contends, is not a curiosity but part of a vital and discernible tradition of modern neo-Augustanism that has been previously overlooked. By tracing these writers' common interest in Horace, John Dryden, and Samuel Johnson, he uncovers important links between seemingly diverse modern poets. Deane challenges the whole interpretation of literary modernism, which has traditionally linked the modern poets to the Romantics and seen both as anti-Augustan. Deane concludes that these modern poets share a ready and pragmatic acceptance of linear time, within which all acts of artistic and social creativity must take place - a crucial factor in both the form and substance of their writings. That art, language, and society are inseparable under such conditions was a bracing thought for the young Auden, but a potentially disturbing one for more recent poets.